Accessory Talar Facet Impingement in Pathologic Conditions of the Peritalar Region in Adults. (October 2014) - Niki, Hisateru; Hirano, Takaaki; Akiyama, Yui; Beppu, Moroe
Introduction: Associations between accessory anterolateral talar facet (AALTF) and sinus tarsi pain in adults have not been reported. This study aimed to investigate the clinical and imaging characteristics of pathologic conditions of the peritalar region in adults with painful accessory talar facet impingement (ATFI). Methods: We included 31 patients (aged 19-75 years) with persistent sinus tarsi pain who underwent surgery and had pathologic conditions of the peritalar region, including adult acquired flatfoot deformity (AAFD; 18 patients), ankle osteoarthritis (8 patients), and ankle instability (5 patients). Continuity between the articular surface of the posterior facet of the talus and AALTF was identified on preoperative computed tomography and magnetic resonance imaging (MRI) of the cartilage. In addition, focal abutting bone marrow edema (FABME) of the talus and calcaneal neck around the AALTF on short TI inversion recovery sequence MRI was confirmed. Subtalar arthroscopy was used to evaluate the AALTF surface characteristics. Pre- and postoperative objective scores were compared. Eight pre- and postoperative radiographic parameters were compared to confirm the effect of foot alignment changes after reconstructions on sinus tarsi pain with ATFI. Pre- and postoperative changes in FABME were compared with 17.1 (7-60) months of follow-up. Results: Subjects underwent accessory facet resection with balancing reconstruction. Arthroscopically, 66% of patients showed a focal defect on the AALTF cartilage surface, and 83% showed attenuation of the posterior capsular ligament. All x-ray parameters in AAFD patients showed significant improvement postoperatively ( P < .001). Mean objective scores improved from 54.0 preoperatively to 91.0 postoperatively ( P < .001). Sinus tarsi pain and FABME were absent in all cases at the final follow-up. Conclusion: AALTF represents a new etiology of subsequent painful intra-articular talocalcaneal impingement. When addressing sinus tarsi pain, it is important to detect the signs of AALTF on MRI of the cartilage and accompanying FABME. Level of Evidence: Level IV, retrospective case series.